Why omitting general public policy exceptions from investment treaties is a setback for the right to regulate - Wolfgang Alschner (Columbia University, Columbia Center on Sustainable Investment (CCSI), 2022)
Responding to a recent Perspective on "The new Canadian Model investment treaty," this article explores the reasons why the omission of general public policy exceptions in investment treaties is a setback for the right to regulate.
Keywords: 330